2011
DOI: 10.2151/sola.2011-033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the East Asian Winter Monsoon Variability on the Surface Cyclogenesis over the East China Sea in Late Winter

Abstract: Using data from the Japanese long-term Re-Analysis project (JRA-25) and the Japan Meteorological Agency Climate Data Assimilation System (JCDAS), we examined how the East Asian winter monsoon variability regulates the surface cyclogenesis in the vicinity of the East China Sea and the Kuroshio Current in late winter. On a monthly basis, the surface cyclone occurrence has a tendency to concentrate over the East China Sea at the strong phase of the East Asian winter monsoon activity, while it disperses zonally al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…) are found to be positive over central China and eastern coastal China between strongest and weakest EAWM years (strongest minus weakest) due to the variations of SHFLX, agree with previous studies who also reported more heat energy transferred to the atmosphere in strong EAWM years[Shiota et al, 2011; …”
supporting
confidence: 92%
See 1 more Smart Citation
“…) are found to be positive over central China and eastern coastal China between strongest and weakest EAWM years (strongest minus weakest) due to the variations of SHFLX, agree with previous studies who also reported more heat energy transferred to the atmosphere in strong EAWM years[Shiota et al, 2011; …”
supporting
confidence: 92%
“…The EAWM‐related SHFLX are found to increase by 3–6 W m −2 over East China and Northeast China (Figure a) and indicate that the larger heat energy is transferred from the surface to the atmosphere by conduction and convection in the strongest EAWM years than those in weakest EAWM years in these regions. The simulated differences in THFLX (SHFLX + LHFLX; Figure e) are found to be positive over central China and eastern coastal China between strongest and weakest EAWM years (strongest minus weakest) due to the variations of SHFLX, agree with previous studies who also reported more heat energy transferred to the atmosphere in strong EAWM years [ Shiota et al ., ; Kim et al ., ] and cooling the surface. Over south China, the less THFLX are found in the strongest EAWM years than those in the weakest EAWM years by up to 4 W m −2 due to the negative variations in LHFLX (Figure c), which illustrates the less heat energy transferred to the atmosphere with the enhanced strength of EAWM in this region.…”
Section: Resultsmentioning
confidence: 69%
“…This narrow band of standard deviation along the Kuroshio is consistent with Xie et al (2002) and Shiota et al (2011), and it is where extratropical cyclones develop along the East China Sea shelf break. According to Shiota et al (2011), the cyclone development along the shelf break is enhanced by a strong winter monsoon, so that the magnitude of standard deviations is likely to depend on the winter monsoon strength measured by, for instance, the East Asian winter monsoon index (SLP difference between Irkutsk, Russia, and Nemuro, Japan; Hanawa et al 1989 First, to validate the model results used in the subsequent analyses, Aikawa in the Sea of Japan, Hachijojima south of Japan Islands, and Naha in the East China Sea (see Fig. 1 for these locations) were selected for comparison between modeled SLP time series and observational counterparts available from the Japan Meteorological Agency website.…”
Section: Standard Deviations Of Surface Vorticity Oversupporting
confidence: 69%
“…5. [ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi (›u e /›x) 2 1 (›u e /›y) 2 p ] of modeled EPT (u e ), as in Yoshiike and Kawamura (2009). For simplicity, we did not use the Eady growth rate, the more appropriate measure of baroclinicity because both measures show a similar pattern over the East Asian marginal seas (Yoshiike and Kawamura 2009;Shiota et al 2011). The 925-hPa EPT map averaged over the six winter seasons from 2002 to 2008 (Fig.…”
Section: A Favorable Condition For High Baroclinicity Above the Yellmentioning
confidence: 99%
“…Their results were consistent with those from this study. Additionally, extratropical cyclones passing to the south of the Kuroshio front often appear (e.g., Adachi & Kimura, 2007;Iizuka et al, 2013;Nakamura et al, 2012;Shiota et al, 2011;Yoshida & Asuma, 2004;Yoshiike & Kawamura, 2009), with their tracks resembling that of the cyclone highlighted in this study. This implies that the situation leading to the outer front formation presented in this study is not rare and that outer fronts often occur.…”
Section: Summary and Discussionmentioning
confidence: 59%